(untitled) (Philological Studies, 2024)
Literary trauma studies place their research focus on the modes in which personal experience is transformed into a literary work, and the role that language and memory play in that transformation. Poetry with its ellipses, symbolism and syntactic syncopations, can capture the most subtle nuances of traumatic experiences, and through them express in words what is initially unspeakable in trauma. This text analyzes the poems from the poetry collection Ordeals by Simona Gruevska - Madžoska, applying the latest theoretical reflections from the field of cultural and literary studies related to the trauma.